Otx2 ChIP-seq reveals unique and redundant functions in the mature mouse retina. - Alexander Samuel; Michael Housset; Bruno Fant; Thomas Lamonerie (PLoS ONE, 2014)
During mouse retinal development and into adulthood, the transcription factor Otx2 is expressed in pigment epithelium, photoreceptors and bipolar cells. In the mature retina, Otx2 ablation causes photoreceptor degeneration through a non-cell-autonomous mechanism involving Otx2 function in the supporting RPE. Surprisingly, photoreceptor survival does not require Otx2 expression in the neural retina, where the related Crx homeobox gene, a major regulator of photoreceptor development, is also expressed. To get a deeper view of mouse Otx2 activities in the neural retina, we performed chromatin-immunoprecipitation followed by massively parallel sequencing (ChIP-seq) on Otx2. Using two independent ChIP-seq assays, we identified consistent sets of Otx2-bound cis-regulatory elements. Comparison with our previous RPE-specific Otx2 ChIP-seq data shows that Otx2 occupies different functional domains of the genome in RPE cells and in neural retina cells and regulates mostly different sets of genes. To assess the potential redundancy of Otx2 and Crx, we compared our data with Crx ChIP-seq data. While Crx genome occupancy markedly differs from Otx2 genome occupancy in the RPE, it largely overlaps that of Otx2 in the neural retina. Thus, in accordance with its essential role in the RPE and its non-essential role in the neural retina, Otx2 regulates different gene sets in the RPE and the neural retina, and shares an important part of its repertoire with Crx in the neural retina. Overall, this study provides a better understanding of gene-regulatory networks controlling photoreceptor homeostasis and disease.